Periodontal bone height of exclusive narghile smokers compared with exclusive cigarette smokers. Issue 1 (1st January 2016) - Khemiss, Mehdi; Khelifa, Mohamed Ben; Rejeb, Mohamed Ben; Saad, Helmi Ben
Abstract : Objective: To compare the periodontal bone height (PBH) of exclusive narghile smokers (ENS) with that of exclusive cigarette smokers (ECS). Methods: Tunisian males aged 20–35 years who have been ENS for more than five narghile-years or ECS for more than five pack-years were recruited to participate in this comparative cross-sectional study. Information about oral health habits and tobacco consumption were gathered using a predetermined questionnaire. Plaque levels were recorded in four sites using the plaque index of Loe and Silness. The PBH was measured mesially and distally from digital panoramic radiographs of each tooth and expressed as a percentage of the root length. A PBH level ≤0.70 was applied as a cutoff reference value signifying bone loss. Student t -test and Chi 2 test were used to compare quantitative and qualitative data of both groups. Results: There were no significant differences between the ENS ( n =60) and ECS ( n =60) groups regarding age and the consumed quantities of tobacco (28±4 vs. 27±5 years, 7±3 narghile-years vs. 8±3 pack-years, respectively). Compared with the ECS group, the ENS group had a significantly higher plaque index (mean±SD values were 1.54±0.70 vs. 1.84±0.73, respectively). However, the two groups had similar means of PBH (0.85±0.03 vs. 0.86±0.04) and tooth brushing frequencies (1.1±0.8 vs. 0.9±0.6 a day, respectively) and had similar bone loss frequencies (15% vs. 12%, respectively). Conclusions: Both ENS and ECS exhibited the same PBH reduction, which means that both types of tobacco smoking are associated with periodontal bone loss.